Ender's game - Card, Orson Scott; Card, Orson Scott; Weber, Sam (Illustrator) (2017)
Once again, Earth is under attack. An alien species is poised for a final assault. The survival of humanity depends on a military genius who can defeat the aliens. But who? Ender Wiggin. Brilliant. Ruthless. Cunning. A tactical and strategic master. And a child. Recruited for military training by the world government, Ender's childhood ends the moment he enters his new home: Battle School. Among the elite recruits Ender proves himself to be a genius among geniuses. He excels in simulated war games. But is the pressure and loneliness taking its toll on Ender? Simulations are one thing. How will Ender perform in real combat conditions? After all, Battle School is just a game. Isn't it?
Third -- Peter -- Graff -- Launch -- Games -- The Giant's drink -- Salamander -- Rat -- Locke and Demosthenes -- Dragon -- Veni vidi vici -- Bonzo -- Valentine -- Ender's teacher -- Speaker for the dead.
"A Tom Doherty Associates book."
"The classic of modern science fiction"--Front cover.
Accelerated Reader AR
Keywords: Wiggin, Ender -- (Fictitious character) -- Fiction; Genetic engineering -- Fiction; War games -- Fiction; Space warfare -- Fiction; Child soldiers -- Fiction